A Complex Insertion Sequence Cluster at a Point of Interaction between the Linear Plasmid SCP1 and the Linear Chromosome of Streptomyces coelicolor A3(2) - Yamasaki, Masayuki (American Society for Microbiology, 2000)
The giant linear plasmid SCP1 can integrate into the central region of the linear chromosome of Streptomyces coelicolor A3(2). Nucleotide sequence analysis around the target site for SCP1 integration in strain M145 identified a total of five copies of four insertion sequences (ISs) in a 6.5-kb DNA stretch. Three of the four (IS468, IS469, and IS470) are new IS elements, and the other is IS466. All of these elements contain one open reading frame which encodes a transposase-like protein. Two copies of IS468 (IS468A and -B) are tandemly aligned at the left end of the cluster. Following these, IS469 and IS466 are located in a tail-to-tail orientation with 69.3% identity to each other. IS470 is located at the right end of the cluster. The activities of IS466 and IS468 were demonstrated by transposition experiments and sequence comparison of several copies, respectively.